2010
DOI: 10.1007/s00405-010-1272-5
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular disorders among adults in a tertiary hospital in Lagos, Nigeria

Abstract: Dizziness is not an uncommon complaint in the Otolaryngological clinics among other symptoms. To a large number of practitioners, the treatment of dizziness remains the same irrespective of the etiology, i.e., anti-vertiginous drugs. The objective of this study was to document the evaluation, causes and treatment of vestibular disorders among our patients. The design includes descriptive prospective study conducted in the Oto-rhino-laryngology and Orthopedic Clinics of Lagos University Teaching Hospital, Lagos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
14
1
1
Order By: Relevance
“…In the study by Somefun et al, 16 i Completeness of outcome data: = below 10% missing data; s = 10% or more missing data; ? = unclear, no information provided.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Somefun et al, 16 i Completeness of outcome data: = below 10% missing data; s = 10% or more missing data; ? = unclear, no information provided.…”
Section: Discussionmentioning
confidence: 99%
“…Эти заболевания составили 94,1% всех случаев периферических вестибулярных расстройств, выявленных у обследованных пациентов. Наши данные подтверждают результаты аналогичных исследований, проведенных в зарубежных клиниках и выявивших значительное преобладание периферических вестибулярных заболеваний среди причин головокружения [13,14]. Вопреки распространенному мнению, цереброваскулярная патология, так часто диагностируемая у пациентов с жалобами на головокружение, встречалась значительно реже и существенно уступала по распространенности периферическим вестибулярным заболеваниям.…”
Section: результаты и обсуждениеunclassified
“…2 Cervical vertigo can be a rare cause of vertigo 3 or it can be among its main causes. 4 In the elderly, Colledge et al suggested that cervical spondylosis is the second most-frequent cause of dizziness, which would be more representative of those who complain of dizziness to their general practitioner. 5 Advocates of vertigo of cervical origin state that cervical vertigo is the most common cause of vertigo; however, there is no diagnostic method to establish whether a patient's vertigo is caused by an underlying neck condition.…”
Section: General Backgroundmentioning
confidence: 99%